LAJU PERTUMBUHAN DAN ANALISA DAYA SAING EKSPOR UNGGULAN DI PROPINSI KALIMANTAN SELATAN - . Safriansyah (Jurnal Ekonomi Pembangunan, 2010)
The objective of this research is to knoe the rate of export growth and the competitive ability of superior export commodity in south kalimantan in 2003-2007. In order to know the growth rate of superior export product in south kalimantan, the researcher used growth analysis, while to analyze the rate of competitive ability of export commodity in south kalimantan, the researcher used Revealed Competitive Advantage (RCA), Revealed Comparative Trade Advantage (RCTA) and Indeks Spesialisasi Perdagangan (ISP) analysis. Based on the research and data analysis, it is known that since 2003 until 2007, the export growth in south kalimantan has always been increasing. The average rate of export in south kalimantan is 25,4% since 2003 until 2007. While the hogest average rate of superior export product is 150, 01% for rubber product.While the lowest average rate is -3,06% for Rotan. The level of export competitive abilty, mining product has the higest RCA index, 6,78 since 2003 until 2007. And the lowest average index is 6,18 for logging product. By using RCTA analysis, the higest average index is 24,89 for mining product since 2003 until 2007. In ISP analysis, the higest average index is 0,99 for mining, while the lowest is 0,44 for Rotan product since 2003-2007.